2010
DOI: 10.1001/archgenpsychiatry.2010.46
|View full text |Cite
|
Sign up to set email alerts
|

Daily Left Prefrontal Transcranial Magnetic Stimulation Therapy for Major Depressive Disorder

Abstract: clinicaltrials.gov Identifier: NCT00149838.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
626
3
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 920 publications
(687 citation statements)
references
References 73 publications
18
626
3
13
Order By: Relevance
“…Finally, we explored the relationship between our connectivity-guided TMS stimulation targets and the current standard clinical procedure for targeting of rTMS for depression [i.e., "the 5-or 6-cm rule"; (22)(23)(24)(25)(26)]. At present, this is the only US Food and Drug Administrationapproved brain rTMS-based treatment for any clinical indication and involves stimulation aimed at the dorsolateral prefrontal cortex, at a site 5-6 cm anterior to the primary motor cortex (M1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we explored the relationship between our connectivity-guided TMS stimulation targets and the current standard clinical procedure for targeting of rTMS for depression [i.e., "the 5-or 6-cm rule"; (22)(23)(24)(25)(26)]. At present, this is the only US Food and Drug Administrationapproved brain rTMS-based treatment for any clinical indication and involves stimulation aimed at the dorsolateral prefrontal cortex, at a site 5-6 cm anterior to the primary motor cortex (M1).…”
Section: Resultsmentioning
confidence: 99%
“…The clinical efficacy of rTMS, however, remains fairly limited, owing to a poor mechanistic understanding of the effects of rTMS and suboptimal targeting of stimulation, which currently makes minimal explicit reference to patients' structural or functional neuroanatomy (44,45). It is therefore intriguing that the MPFC-regulating CEN node (pMFG) was located 5-6 cm anterior of primary motor cortex, consistent with current methods for localizing the clinical rTMS stimulation site (25,26). Thus, because connectivity-guided modulation of this node selectively regulates the MPFC/DMN, our results may serve as a unique platform for circuit-driven interventions in humans, including for depression.…”
Section: Discussionmentioning
confidence: 97%
“…Concerning RCTs on TMS, five articles out of 97 detailed the possibility for patients to miss one or more sessions in their methodology and one article reported missed visits as a reason for dropout in the study flowchart. George et al (2010) defined completers as patients having less than 4 rescheduled, missed or partially completed sessions, and fully adherent as patients having a maximum of 1 rescheduled, missed, or partially complete sessions (n=15 sessions) [23]. Out of 190 patients, 120 were fully adherent (63%) and 154 were considered as completers (81%).…”
Section: Findings' Summarymentioning
confidence: 99%
“…As novel neuromodulation therapies are introduced, it is imperative that clinicians in the field of Psychology and Psychiatry carefully weigh the evidence base, risks and benefits before applying these new treatments to our patients Neuromodulation therapies that have emerged include: (1) Transcranial Magnetic Stimulation (rTMS or TMS); Vagal Nerve Stimulation (VNS), Deep Brain Stimulation (DBS), and; Transcranial Direct Current Stimulation (tCDS) [1]. These four neuromodulation therapies have been proposed as treatments for several neuropsychiatric disorders, specifically: (1) TMS for recurrent major depressive disorder (MDD) [2,3] and refractory auditory hallucinations/persistent negative symptoms in schizophrenia [4][5][6]; (2) VNS for refractory MDD [7]; (3) DBS for treatment-refractory obsessive-compulsive disorder (OCD) [8] and treatment-refractory unipolar and bipolar depression [9,10], as well as; tCDS for MDD [11,12] and schizophrenia [13]. The evidence to support the use of these neuromodulation modalities for these indications varies in strength.…”
mentioning
confidence: 99%
“…A nonindustry sponsored replication study [3] using a non-proprietary system: had a prospective, multisite, randomized, active shamcontrolled design; 190 antidepressant drug-free patients with unipolar MDD were randomized to active TMS or sham TMS (with a non-proprietary system); showed an overall retention rate of 88% (90% sham and 86% active); demonstrated a significant effect of active TMS treatment on the proportion of remitters (14.1% active rTMS and 5.1% sham) (P=.02); the odds of attaining remission was 4.2 times greater with active TMS than with sham; concluded that left prefrontal rTMS as monotherapy produced statistically significant and clinically meaningful antidepressant therapeutic effects greater than sham with minimal side effects. Subsequently, another metanalysis that included the two aforementioned studies and any other trials [17], a metanalysis of all the metalysise yet conducted [18], and an independent review commissioned by the U.S. Department of Health and Human Services [19], supported the safety and efficacy of TMS for MDD.…”
mentioning
confidence: 99%